A comparative study of bilateral ilioinguinal and iliohypogastric nerve block for postoperative analgesia in lower segment cesarean section: bilateral ilioinguinal and iliohypogastric nerve block for postoperative analgesia - Shaon, Afsana Hossain; samad , Mahbuba Binti Abdis; Dey, Chayan Kumar (Journal of the Medical College for Women & Hospital, 2025)
Background: Post-cesarean pain management remains challenging in resource-limited settings. This study evaluated the efficacy of bilateral ilioinguinal and iliohypogastric nerve blocks for post-cesarean analgesia in Bangladesh.Materials and Method: A prospective randomized controlled trial was conducted at Mymensingh Medical College Hospital, Mymensingh (MMCH), involving 50 women undergoing elective cesarean section. Participants were randomized to receive either bilateral nerve blocks with 0.25% bupivacaine (Group A, n=25) or standard post-operative care (Group B, n=25). Primary outcomes included pain scores, analgesic (tramadol) consumption, and time to mobilization.Results: Group A demonstrated significantly lower pain scores (mean VAS 2.8±0.9 vs 5.4±1.2, p<0.001), reduced tramadol consumption (87.5±25.4mg vs 175.0±32.6mg, p<0.001), and earlier mobilization (6.2±1.1 vs 8.9±1.4 hours, p<0.001). Quality of Recovery scores were superior in Group A (122.4±8.7 vs 98.6±11.2, p<0.001), with no significant complications.Conclusion: Bilateral ilioinguinal and iliohypogastric nerve blocks provide effective post-cesarean analgesia, reducing opioid requirements and improve recovery parameters. The technique presents a viable option for enhanced recovery protocols in developing nations. J Med Coll Women Hosp.2025; 21 (1):23-31